ROCK PHYSICS SIMULATION OF RESERVOIR SAND_K2 IN ‘KUTI’ FIELD, DEEP OFFSHORE NIGER DELTA - Oladele, Sunday; Onayemi, John Ramon; Rotimi, Salami (FUDMA Journal of Sciences, 2024)
Rock physics modelling has been employed in studying the elastic behaviors of reservoir SAND_K2 in the ‘KUTI’ Field, Niger Delta under a plausible production scenario of increasing water saturation. The study aimed to investigate how variation in reservoir fluid saturation will influence seismic attributes and determine the characteristics of expected time-lapsed (4-D) seismic signals that may be generated due to the effects of production. Multivariate cross-plot analyses of petro-elastic parameters were carried out to establish the seismic characteristics of the target reservoir with different pore fluids in its natural state before production. Fluid replacement modelling was applied to calculate measurable changes in the reservoir’s seismic characters by steadily increasing the water saturation from its initial value to 100%. Synthetic logs of petro-elastic parameters were created for different values of water saturation and combined into property cross-plots to predict the dynamic seismic response of the reservoir as brine gradually replaced hydrocarbon. Results showed that fluid changes from hydrocarbon to brine produced significant and quantifiable seismic signatures for time-lapse monitoring investigation. At some future points in the production history of the field under increasing water saturation conditions, the density, P-wave velocity and acoustic impedance of SAND_K2 increase and produce a negative seismic difference data of P-wave amplitude. Based on the responses of reservoir SAND_K2 under modelled production conditions, the study concluded that rock physics analysis can help to optimize and enhance the success of time-lapse monitoring of the KUTI Field.